Chemical engineering and processing (Elsevier Science Pub. Co, 1984)
"Chemical engineering and processing is a journal intended for practising engineers in industry and academia. The aim of the published articles is to demonstrate how novel discoveries, developments and theories may be used for improved analysis and design of chemical engineering equipment and processes. The journal offers space for articles on any branch of chemical engineering and is particularly concerned with mechanical, thermal and chemical unit operations, but also includes analyses relating to environmental chemical engineering and sustainable industrial development."
Keywords: Chemical engineering : Periodicals